Development of Creative Potential of Pupils with Mixed Specific Developmental Disorders - Zhilova, Yuliya P.; Kulesza, Eva Ðœaria; Namazbayeva, Zhamila I.; Likhodedova, Lyudmila N.; Bezhina, Viktoriya V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The aim of the article is an alternative approach to develop the creative potential of pupils with mixed specific developmental disorders (MSDD). Background: Modern special education should solve one of the urgent problems that are to help children with special educational needs to activate their creative potential. Method: Following the elaborated structure of the development of the creative potential of children with MSDD for the diagnosis of each component, we have selected the following methods: the E. Torrence Creative Thinking Test “Incomplete figures”, the graphic technique “Cactus”, the technique “Ladder”. Results: It organized an empirical study on the creative potential of 10-11-year-old pupils with MSDD with the use of pedagogical experiment. A model of supporting the development of creative potential was developed. In this model, special pedagogical conditions which included a personality-oriented approach, creative educational environment, and pedagogical support, were implemented. The pedagogical experiment was conducted in the framework of the study involving seven schools of Kostanay region of the Republic of Kazakhstan. Conclusion: The results revealed the significant growth in pupils’ creativity when implementing the model with the set of pedagogical conditions.